Determination of amphotericin B in PLA-PEG blend nanoparticles by HPLC-PDA - Caroline Danziato Rodrigues; Najeh Maissar Khalil; Rubiana Mara Mainardes (Universidade de São Paulo, 2014)
In this work, we developed and validated an effective reversed-phase HPLC method with photodiode array (PDA) detection for the quantitative analysis of amphotericin B (AmB) in poly(lactide)-poly(ethylene glycol) (PLA-PEG) blend nanoparticles. Chromatographic runs were performed on a reverse phase C18 column using a mobile phase comprising a 9% acetic acid and acetonitrile mixture (40:60, v/v) under isocratic elution with a flow rate of 1 mL/min. AmB was detected at a wavelength of 408 nm. The validation process was performed considering the selectivity, linearity, precision, accuracy, robustness, limit of detection (LOD) and limit of quantitation (LOQ) of the method. A concentration range of 1-20 µg/mL was used to construct a linear calibration curve. The LOQ and LOD were 55 and 18 ng/mL, respectively. The mean recovery of AmB from the samples was 99.92% (relative standard deviation (RSD) = 0.34%, n=9), and the method was robust for changes in the flow rate of the mobile phase (maximum RSD=4.82%). The intra- and inter-assay coefficients of variation were less than 0.59%. The method was successfully used to determine the entrapment efficiency of AmB in PLA-PEG blend nanoparticles.